2020
DOI: 10.21203/rs.3.rs-32610/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk perception and Emotion evaluation of Health care workers varied during different periods of COVID-19: a repeated cross-sectional research

Abstract: Background Health care workers (HCWs) on the front line of the COVID-19 were facing greater risks than usual, and their perception of these risks could also be an important part of their anti-epidemic work. This study aimed to examine risk perception and negative emotions of during two periods of the COVID-19 and emphasized emotional intervention management of HCWs impacting the risk perceptions and self-protection and would provide plausible intervention points for the psychological aid under a stressful cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
3
0
0
Order By: Relevance
“…The public psychological status differed among different periods of the COVID-19 pandemic; this result was consistent with other studies Zhao et al, 2020;Yin et al, 2021). This study also illustrated the decline of pessimistic sentiment during the regular epidemic prevention and control period, which has also been revealed by other scholars (Jia and Liu, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The public psychological status differed among different periods of the COVID-19 pandemic; this result was consistent with other studies Zhao et al, 2020;Yin et al, 2021). This study also illustrated the decline of pessimistic sentiment during the regular epidemic prevention and control period, which has also been revealed by other scholars (Jia and Liu, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Those who exhibited self-protection (Type 1) were willing to overcome the challenges of a pandemic; however, they demonstrated a psychologically defensive attitude. The characteristics of Type 1 affirm the findings from a previous study, which found that individuals' perception of risks is influenced by their intuitive judgments, subjective emotions, and understanding of objective risks in the outside world [21]. In addition, the participants strongly agreed with the Q-item: "Q30.…”
Section: Discussionsupporting
confidence: 83%
“…An examination of their interviews revealed that, to them, a nurse's sense of duty was not unconditional; rather, it implied doing one's best to serve others while protecting oneself. Moreover, Type 1 supports the finding that an individual's ability to perceive risks is vital for adjustment and self-protection [21]. Furthermore, having a selfprotective attitude can enhance an individual's psychological comfort and make them take precautions [22,23].…”
Section: Discussionsupporting
confidence: 56%